Proviruses with Long-Term Stable Expression Accumulate in Transcriptionally Active Chromatin Close to the Gene Regulatory Elements: Comparison of ASLV-, HIV- and MLV-Derived Vectors - Dalibor Miklík; Filip Šenigl; Jiří Hejnar (Viruses, 2018)
Individual groups of retroviruses and retroviral vectors differ in their integration site preference and interaction with the host genome. Hence, immediately after infection genome-wide distribution of integrated proviruses is non-random. During long-term in vitro or persistent in vivo infection, the genomic position and chromatin environment of the provirus affects its transcriptional activity. Thus, a selection of long-term stably expressed proviruses and elimination of proviruses, which have been gradually silenced by epigenetic mechanisms, helps in the identification of genomic compartments permissive for proviral transcription. We compare here the extent and time course of provirus silencing in single cell clones of the K562 human myeloid lymphoblastoma cell line that have been infected with retroviral reporter vectors derived from avian sarcoma/leukosis virus (ASLV), human immunodeficiency virus type 1 (HIV) and murine leukaemia virus (MLV). While MLV proviruses remain transcriptionally active, ASLV proviruses are prone to rapid silencing. The HIV provirus displays gradual silencing only after an extended time period in culture. The analysis of integration sites of long-term stably expressed proviruses shows a strong bias for some genomic features—especially integration close to the transcription start sites of active transcription units. Furthermore, complex analysis of histone modifications enriched at the site of integration points to the accumulation of proviruses of all three groups in gene regulatory segments, particularly close to the enhancer loci. We conclude that the proximity to active regulatory chromatin segments correlates with stable provirus expression in various retroviral species.